The local mineral potential from East Lampung - Indonesia: the use of basalt rock as a stone meal for cassava plant - Yusup Hendronursito; Junita Barus; Muhammad Amin; Muhammad Al Muttaqii; Tumpal Ojahan Rajagukguk; Kusno Isnugroho; David Candra Birawidha (Brawijaya University, 2019)
Indonesia has an abundant amount of basalt rocks resources, including in East Lampung Regency of Lampung Province. This basalt has not been used optimally and only be used as a foundation. The use of basalt as soil fertilizer also known as the stone meal. This study focused on the effect of using basalt dust on the growth and development of organic fertilizer application for the cassava plant. This study is to support the local government policies that declared Lampung as a national development centre of cassava, with a production rate of 30.8% of the national production of cassava. Basalt powder was characterized using test petrograph and X-ray Fluorescence (XRF) for a description of microscopic and chemical composition. The test results were used to determine the chemical composition of rock classification using the TAS diagram. The experiments of applying fertilizer on cassava crops in the demonstration plots 8 treatment x 3 repetitions were conducted by adding the percentage by weight of the basalt towards organic fertilizer between 0% (control 1), 10%, 20%, 30%, 40%, 50%, 60%, and without treatment (control 2). The results indicated that basalt from East Lampung is classified as olivine Tholeite basalt which is rich in CaO, Mg and Na2O + K2O. The growth rate of cassava plants which are affected by basalt powder presentation is characterized by a value which is higher than the value of CGR control, and recommended to not exceed 10% of the weight of basalt fertilizer.